2011
DOI: 10.12928/telkomnika.v9i1.683
|View full text |Cite
|
Sign up to set email alerts
|

Partial Discharge Phase Distribution of Palm Oil as Insulating Liquid

Abstract: Abstrak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…One of the studies reported that RBDPO Olein had almost the same characteristics as mineral oil [38]. The PD test was carried out based on needle-plane electrodes configuration with a 20 mm gap distance and an acrylic with a thickness of 15 mm was placed in between electrodes to prevent breakdown [35].…”
Section: Partial Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…One of the studies reported that RBDPO Olein had almost the same characteristics as mineral oil [38]. The PD test was carried out based on needle-plane electrodes configuration with a 20 mm gap distance and an acrylic with a thickness of 15 mm was placed in between electrodes to prevent breakdown [35].…”
Section: Partial Dischargementioning
confidence: 99%
“…One of them is the PD pulses of RBDPO Olein spread in a much wider area than mineral oil. Secondly, the phase shift of PD occurrence for RBDPO Olein is bigger than mineral oil [38]. It was suggested that the phenomenon is due to the viscosity where the space charges in RBDPO Olein diffused into electrodes much slower than in mineral oil [38].…”
Section: Partial Dischargementioning
confidence: 99%
“…Minyak mineral adalah minyak isolasi yang bahan dasarnya berasal dari minyak bumi yang diproses dengan cara destilasi sehingga mempunyai sifat sebagai isolator dan juga sebagai pendingin [7]. Minyak mineral sulit terurai secara alami oleh migroorganisme dan rentan terhadap bahaya kebakaran [8]. Minyak isolasi mineral banyak digunakan pada transformator daya, kabel, pemutus daya (CB) dan kapasitor [9].…”
Section: Pendahuluanunclassified
“…The high electric field necessary to produce a partial discharge is attained by utilising a needle plane electrode configuration. Since the electric field under needle plane configuration is non uniform, it produces maximum electric field [8]. To implement vegetable oils in high voltage apparatus, it is necessary to identify the PD characteristics using a needle plane configuration in vegetable oils.…”
Section: A Prpd Patternmentioning
confidence: 99%